PENGEMBANGAN ERA DIGITAL MARKETING KELOMPOK UMKM PEREMPUAN SRIKANDI GILINGAN BANJARSARI SURAKARTA - Amalia, Naili; Sunarso, Sunarso; Aprian Aditama, Rizky Ramadhan (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The perpetrators of the Women's Srikandi Gilingan MSME group in Banjarsari, Surakarta, are classified as living in densely populated villages with a minimal economy. So far, the Women's Srikandi Gilingan Banjarsari Surakarta UMKM group has been active in making karak crackers. Not all members are involved in making these karak crackers. In the near future, there will be a development of processed catfish products into nuggets as a driver of economic growth for the Srikandi Gilingan Women's MSME group, Banjarsari, Surakarta. The obstacle is the lack of knowledge of the MSME group in marketing their products. The low level of digitalization has made the Women's Srikandi Gilingan Banjarsari Surakarta UMKM group not have a wide range of buyers. By offering the concept of a digital marketing strategy and implementing The Seven Laws, it will provide convenience for the Women's Srikandi Gillingan Banjarsari Surakarta MSME group in optimizing product sales. The results of the FGD formulation show that there are several steps that must be taken by members, including understanding social media channels, making publications on various social media, managing channels and consistently updating, increasing traffic, starting from existing social media. The greatest hope for this implementation will have a positive impact on the development of Srikandi's MSMEs. Kata kunci: Digital Marketing, UMKM Srikandi